Synergy of Islamic Education Management and Administration in Increasing the Effectiveness of Kitab Kuning Learning Program at Pondok Pesantren Darussalim Bati-Bati - Nur Sobah; Jamil Jamil (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the synergy between management and Islamic educational administration in improving the effectiveness of kitab kuning instruction at Pondok Pesantren Darussalim Bati-Bati. The research is grounded in the growing need for pesantren to balance classical Islamic scholarly traditions with modern managerial systems in order to respond effectively to contemporary educational challenges. Employing a qualitative case study design, the study involved four groups of informants: pesantren leaders, administrative staff, kitab kuning teachers, and students, selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that synergy between management and administration is established through intensive communication, routine evaluation, and scheduled coordination, resulting in a cooperative and responsive institutional work structure. The administrative unit plays a crucial role in providing learning facilities, arranging schedules, preparing academic documentation, and bridging managerial policies with instructional implementation, thereby ensuring that kitab kuning learning runs in a more orderly, efficient, and directed manner. Challenges were identified in limited human resources and administrative technology, however capacity-building efforts through training and improved archiving systems positively contributed to governance quality. The study recommends strengthening managerial training, gradual digitalization of administrative processes, and reinforcing cross-unit coordination as strategic steps for pesantren development. This research contributes to enriching the literature on the integration of management and Islamic educational administration.